Pengaruh Injeksi Introvit-E-Selen terhadap Lama Force Molting dan Hen Day Ayam Isa Brown - Nur Saidah Said; Sulmiyati Sulmiyati; Deka Uli Fahrodi (Universitas Sulawesi Barat, 2020)
The aim of this study was to determine the effect of Intovit-E-Selen injection on the length of force molting and Hen Day of Isa Brown hens. The experimental animal used was 80-week-old Isa Brown hens. A total of 80 Isa Brown hens were divided into 4 treatments with 20 replications. The treatments consisted of P0 (0.3 ml Phosphate Buffer Saline), P1 (0.3 ml Intovit-E-Selen Injection), P2 (0.6 ml Intovit-E-Selen Injection), and P3 (0.9 ml Intovit-E-Selen Injection). The study was conducted by calculating the length of force molting and Hen Day. The research results were analyzed using ANOVA, followed by further tests using the Duncan test. The results showed that the treatment of P3 (0.9 ml of Introvit-E-Selen Injection) had an influence on the length of force molting with an average value of 30.55 ± 2.74 and the treatment of P2 (0.6 ml of Introvit-E-Selen Injection) had an influence on Hen Day with an average value of 80.25 ± 1.48. Introvit-E-Selen injection in Isa Brown chickens can shorten the time of force molting and increase the percentage of Hen Day.